Clinical Efficacy of a Topical Gel for the Treatment of Minor Oral Ulcers: A Triple-Blind Randomized Controlled Trial - Felice Lorusso; Nicolai Gianluca; Antonio Scarano (Applied Sciences)
Background: Recurrent aphthous stomatitis (RAS) has been recognized as a pathology characterized by ulcerations of the oral mucosa with a wide cross-prevalence in the general population. The aim of the present investigation was to investigate a new gel formulation for the treatment of minor oral ulcers after 2 weeks of treatment. Materials and Methods: A randomized triple-blinded controlled trial was designed for the present purpose. A total of two different study groups was conceptualized: group I (placebo) and group II (active treatment). After the enrolment process, the subjects were included in a domiciliary treatment and evaluated by a blinded operator to clinical scoring and thermography assessment at the baseline, after 1 week, and 2 weeks. Results: A total of 60 patients were observed and treated in the present study. The mean age of the patients was 34.91 ± 7.27 years old for a total of 38 females and 22 males. At 1 and 2 weeks, a significant difference in clinical scoring was observed comparing group I and group II (p < 0.05). A significant reduction in pain score was detected in group II patients (p < 0.05) after the topical gel administration. Conclusions: According to the findings of this randomized trial, the gel treatment showed a significant decrease in the signs and symptoms of oral ulcerations and could be considered useful to ameliorate the clinical course of the disease.